Efektivitas Ekstrak Etanol Herba Patik Emas (Euphorbia heterophylla L.) dalam Menurunkan Kolesterol Total Pada Tikus Jantan Obesitas terinduksi Diet Tinggi Lemak. - Novembrina, Metrikana; Wahyuni, Tri; Anggrahini, Siti Nur Muthia; Bulu, Atalia Tamo Ina (Jurnal Farmasi & Sains Indonesia, 2024)
Obesity can cause various health problems such as cardiovascular disease and methabolic syndromme (insuline resistance, type 2 diabetes, hypertension und dyslipidemia). Various drug treatments have also been introduced into the community such as simvastatin, gemfibrozil and klorfibrat. These medicines are also considered unsafe if it is used permanently or excessively. Obesity can also bring about dyslipidemia. Hence, the bioactive agent which can burn the visceral fat is definetely needed. In Indonesia there is a great number of weeds which have been identified as a plant that has certain pharmacological effect in human’s body. One of them is wild poinsettia (Euphorbia heterophylla L.) which has also been proven to be effective as an antioxidant and blood glucose-lowering agent through some studies. This was a laboratory experimental study with a post-test only controlled group design. A number of 30 wistar strain white male rats were devided into 6 groups. Group 1 was normal control, group 2 was negative control (CMC Na 0,5 %), Group 3 was a positive control (gemfibrozil), group 4,5 and 6 were the ethanolic extract of wild poinsettia’s herbs in the doses of 250, 500 and 750 mg/kgBW respectively. Previously the total cholesterol level was measured to all testing animals. Before the trial, all testing animals except normal control were given high fat diet for two weeks. The total cholesterol and the body weight were then measured to observe the increase of the level. To the group 2,3,4,5 and 6 then were given the plecebo (CMC Na 0,5%), gemfibrozil, the extracts of 250, 500, and 750 mg/kgBW respectively for two weeks. The body weight and the total cholesterol were then measured again. The results showed that the ethanol extract of the wild poinsettia herb’s extract at a dose of 250 mg / kgBW was effective in reducing total cholesterol levels compared to the negative control. The dose of 750 mg / kgBW showed a maximum lowering effect of total cholesterol levels. Based on the results, it can be concluded that the ethanol extract of wild poinsettia has effectiveness in reducing total cholesterol levels of obese male rats induced by a high-fat diet.